PERLINDUNGAN HUKUM TERHADAP HAK CIPTA MENURUT PASAL 12 UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA DI INDONESIA - Akbar, Fajar Alamsyah; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The portrait is one of the works protected by copyright legislation, namely Act (UU) No. 28 of 2014 about copyright. However in practice often happens to violations of copyright or portrait photography is the property of a person or the copyright holder, which is called model or artist management taken by the perpetrator of the offence without the written consent of the copyright holder. Problems that arise now is how legal protection over the portrait. This research includes types of sociological research, which is research by examining its legal aspects to look at legislation and comparing with the implementation on the ground gained by way of surveys. Analysis of the research material in this thesis using qualitative methods, in order to draw conclusions by using deductive methods.Then from the results showed that the entire creation works of photography or portrait produced by Act (UU) No. 28 of 2014 about copyright, all concern parties can prove that his work is his creation, which can be proven by way of registering creations or in any way in accordance with the laws and regulations that govern it. And in the completion of the portrait is a file a lawsuit as compensation demands to the Court of Commerce and in the implementation of the rules of criminal law can be made by an authorized investigator, but most of the management model of resolving the problem of infringement of his work with the line of non litigation (other than the Court) or in a family.Key Words: Copyright protection - Portrait - Taking illegally